MODERASI KEDEKATAN SUPERIOR DAN SUBORDINAT PADA PARTISIPASI ANGGARAN TERHADAP SENJANGAN ANGGARAN DALAM UPAYA MENINGKATKAN KINERJA MANAJERIAL - Susandra, Farizka; Mukmin, Mas Nur; Warizal, Warizal (Jurnal Akunida, 2021)
This study examines the proximity factor between the superior and subordinate as a moderating variable that is expected to moderate the relationship of budgetary participation and slack on the local government budget in order to improve managerial performance. The data used in this study is the primary data. Data collection using questionnaires and in-depth interviews with related parties. Respondents of this research are department heads in SKPD located in Bogor City. The sample was 71 respondents. Budgetary participation, budgetary slack, managerial performance, and superior proximity and subordinates in analysis using SEM PLS with WARP-PLS 6.0 software. The results of this study indicate the performance and budget participation has a positive relationship. Budget slack may be able to mediate the relationship with the budget with a 0.05 significance. In addition, there are interesting findings that high-level subordinate relationships can increase budget participation and reduce budgetary slack, while low-level subordination relationships can reduce the level of budget participation and increase budgetary constraints. As per the statistics that the Exchange Member Theory of proximity or subordinates can moderate the relationship between budgetary participation and budgetary slack to improve managerial performance.